2022
DOI: 10.1159/000525480
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Occult Hepatitis B Virus Infection in Blood Donors with Negative ID-NAT in Switzerland

Abstract: <b><i>Introduction:</i></b> Screening of hepatitis B surface antigen (HBsAg) and individual-donation nucleic acid amplification testing (ID-NAT) of blood donors have become standard to detect hepatitis B virus (HBV) infection. However, there is still a residual risk of HBV transmission by blood components of donors suffering from occult HBV infection (OBI). Therefore, many countries implemented universal testing of anti-HBV core antigen (anti-HBc) antibodies in order to increase blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
1
1
Order By: Relevance
“…The DNA positivity rate in the current study of 8/412 (1.9%, CI [0.8–3.8]) (Figure 5) is slightly lower than a Swiss study's finding of 7/124 (5.6%, CI [2.3–11.3]; p = 0.055) of anti‐HBc‐positive donors with detectable DNA 20 despite our more sensitive assay. Moreover, that study did not stratify by anti‐HBs levels, where blood donations with levels less than 100 IU/L are considered more infectious 8 and more likely to contain HBV DNA.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The DNA positivity rate in the current study of 8/412 (1.9%, CI [0.8–3.8]) (Figure 5) is slightly lower than a Swiss study's finding of 7/124 (5.6%, CI [2.3–11.3]; p = 0.055) of anti‐HBc‐positive donors with detectable DNA 20 despite our more sensitive assay. Moreover, that study did not stratify by anti‐HBs levels, where blood donations with levels less than 100 IU/L are considered more infectious 8 and more likely to contain HBV DNA.…”
Section: Discussioncontrasting
confidence: 87%
“…Moreover, that study did not stratify by anti-HBs levels, where blood donations with levels less than 100 IU/L are considered more infectious8 and more likely to contain HBV DNA. This suggests a lower but still significant proportion of OBI donors in England compared to Switzerland, which follows the lower anti-HBc positivity rate amongst all blood donors 7,20. Considering the DNA positivity rate in our study cohort, an average of 106 [45-213] anti-HBc-positive donations would be DNA-positive per year based on an average of 1 864 484 yearly…”
mentioning
confidence: 67%
“…4 , current policy misses about 22.8% of anti-HBc positive donors, 3 % of whom may have a higher risk of transmission due to presence of HBV DNA. A recent study on Swiss blood donors found that some occult HBV infections with potential transmission risk were missed by HBsAg and ID NAT [ 31 ]. Introducing anti-HBc testing along with ID-NAT testing can greatly reduce the risk of transfusion-mediated transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Крупномасштабное исследование среди доноров компонентов крови в Канаде (обследованы 1 401 603 первичных доноров с 2005 по 2020 год) показало, что распространённость оккГВ среди них составляла 0,004% [16] . В Швейцарии среди доноров с первичным отрицательным анализом на HBsAg и ДНК ВГВ, которым в последующем провели повторный ПЦР анализ для выявления ДНК вируса после концентрирования плазмы крови, распространённость HBsAg-негативного ГВ равнялась 0,06% (у 7 из 11 432 доноров) [17] .…”
unclassified